Lamina‐specific properties of spinal astrocytes. Issue 7 (10th March 2021) - Kronschläger, Mira T.; Siegert, Anna S. M.; Resch, Felix J.; Rajendran, Pradeep S.; Khakh, Baljit S.; Sandkühler, Jürgen
Abstract: Astrocytes are indispensable for proper neuronal functioning. Given the diverse needs of neuronal circuits and the variety of tasks astrocytes perform, the perceived homogeneous nature of astrocytes has been questioned. In the spinal dorsal horn, complex neuronal circuitries regulate the integration of sensory information of different modalities. The dorsal horn is organized in a distinct laminar manner based on termination patterns of high‐ and low‐threshold afferent fibers and neuronal properties. Neurons in laminae I (L1) and II (L2) integrate potentially painful, nociceptive information, whereas neurons in lamina III (L3) and deeper laminae integrate innocuous, tactile information from the periphery. Sensory information is also integrated by an uncharacterized network of astrocytes. How these lamina‐specific characteristics of neuronal circuits of the dorsal horn are of functional importance for properties of astrocytes is currently unknown. We addressed if astrocytes in L1, L2, and L3 of the upper dorsal horn of mice are differentially equipped for the needs of neuronal circuits that process sensory information of different modalities. We found that astrocytes in L1 and L2 were characterized by a higher density, higher expression of GFAP, Cx43, and GLAST and a faster coupling speed than astrocytes located in L3. L1 astrocytes were more responsive to Kir4.1 blockade and had higher levels of AQP4 compared to L3 astrocytes. In contrast, basic membrane properties, network formation, and somatic intracellular calcium signaling were similar in L1–L3 astrocytes. Our data indicate that the properties of spinal astrocytes are fine‐tuned for the integration of nociceptive versus tactile information. Main Points: In‐depth characterization of spinal astrocytes in the upper dorsal horn of mice. Distinct lamina‐ and circuit‐specific properties of spinal astrocytes. Fine‐tuning of astrocytic properties for the integration of nociceptive versus tactile information.